Detection of Rashba field using a rotational applied field - Jang, Hyun Cheol; Park, Youn Ho; Koo, Hyun Cheol; Kim, Hyung-jun; Chang, Joonyeon; Kim, Hijung (AMER INST PHYSICS, 2011)
The intrinsic Rashba field in an InAs quantum well is observed using a potentiometric geometry in which a circular shaped permalloy electrode is utilized with a rotational applied field. From the ratio of the curve shift to the applied field and the amplitude of potentiometric signal, a Rashba field of 8.84 T can be estimated. This method is a very simple and accurate alternative to quantitatively observe the Rashba field. (C) 2011 American Institute of Physics. [doi:10.1063/1.3537944]
Keywords: SPIN-ORBIT INTERACTION; TRANSPORT; SILICON